AGE assessment of interactions between climate change policy instruments and pre-existing taxes: the case of Ireland. (29th August 2011) - Wissema, Wiepke; Dellink, Rob
We introduce a computable general equilibrium model for Ireland to investigate the impact of climate policy on the Irish economy, taking special notice of interactions with the existing tax structure. To this end, we extend the model with a detailed representation of the tax system using separate tax data on all transactions, both intermediate and final demand. We simulate the implementation of auctioned CO2 emissions trading and specific CO2 taxation in Ireland and compare different methods to recycle the revenues. The extended tax specification facilitates a thorough second-best analysis.